(untitled) (Research, Society and Development, 2021)
Hyperpneumatization of the maxillary sinus is a factor that complicates the insertion of implants in the posterior region of the maxilla. Prior maxillary sinus floor elevation is an alternative that will enable implant placement in these cases. However, intraoperative complications may occur, with the perforation of the Schneider membrane being the most common. Several maneuvers for the management of sinus membrane perforations are described in the literature, making it possible to repair and perform the grafting procedure during the same surgical time. Among the forms of repair, the use of leukocyte and platelet rich fibrin (L-PRF) membranes has been shown to be a treatment option with interesting and promising results to achieve repair. This article describes a clinical case in which the perforation of Schneider’s membrane was repaired with L-PRF membranes and the procedure was performed without postoperative complications, enabling the subsequent insertion of implants and successful rehabilitation of the patient.